Penerapan Media Audio Visual untuk Meningkatkan Kemampuan Bahasa Inggris pada Anak Usia Dini Studi Kasus di PAUD Al-Ashar - Handayani, Arista; Agustiningrum, Maria Denok Bekti; Sukiram, Muhammad (Universitas Ivet, 2024)
This study aims to evaluate audiovisual media's effectiveness in improving English language skills in early childhood at PAUD Al-Ashar. The study employs a Classroom Action Research (CAR) design involving 15 children aged 5-6 years as subjects. Data were collected through direct observation and field notes during the learning process. The results indicate a significant improvement in the children's English language skills, particularly in recognizing basic vocabulary and its context. Audiovisual media has proven effective in creating an interactive and engaging learning environment, which encourages active participation from the children throughout the learning process. This study suggests that early childhood educators consider the implementation of audiovisual media as an effective tool in teaching English.